Hope, enthusiasm, and skepticism: Public emotional representation of female leaders' reputation in the 2024 East Java regent elections - Syam Maella, Nurannafi Farni; Farida, Farida; Zulaikha, Zulaikha; Adi Nugraha, Kevin; Setia Wardhani, Widya Desary (Universitas Bunda Mulia, 2025)
The nomination of female incumbent regional heads has not escaped public scrutiny and judgment on digital media ahead of the 2024 regional head elections. Analyzing public emotions through sentiment analysis and capturing mass opinions via social media is an interesting phenomenon, especially considering the persistent gender challenges and barriers in Indonesian politics. This research aims to explore how the public responds to the leadership of a currently serving female leader who will run for re-election in the 2024 period and whether the emotions that arise are related to performance, gender, or a combination of both. The research method used is social network analysis to analyze key actors with text analysis from social media platforms such as Instagram, Facebook, and online news. In data collection, the researchers used the website https://esuit.dev/, as well as two software programs, Gephi and Orange, to conduct metric analysis and text analysis of comments from social media. We conducted this research on the regional heads of Blitar Regency, Nganjuk Regency, and Lumajang Regency in East Java Province, Indonesia. This study found that performance factors, understanding of gender issues, and social stereotypes attached to female leaders influence public emotions towards incumbent female leaders. While successful policies and sustained leadership drive significant support, negative sentiments related to traditional gender norms also emerge. These findings illustrate that although incumbent female leaders can gain appreciation for their performance, they also face challenges in overcoming gender biases associated with their work. The implications of this research provide important insights into the dynamics of public emotions in the 2024 regional elections and the significance of political education that can help reduce gender bias in Indonesia's local elections.